Płeć jako dzieło sceniczne non-fiction. "Dobrze ułożony młodzieniec" Jolanty Janiczak i Wiktora Rubina (studium przypadku) - Popczyk-Szczęsna, Beata (Zagadnienia Rodzajów Literackich, 2024)
The Well-Behaved Young Man from Teatr Nowy in Łódź is an example of radical artistic practice in an institutional theatre, which involves performing the experience of a transsexual person by another transsexual person. The author of the text, Jolanta Janiczak, and the director, Wiktor Rubin, created a literary and theatrical non-fiction form in which the presentation of the life of an individual who does not identify with the assigned gender is also a manifest against homo- and transphobia. The article considers the experience of gender, the construction of gender and ways of representing it in a play about events from the past. The Well-Behaved Young Man belongs to the trend of performances inspired by biographies, it is an example of (auto)biography performance, because the presented fragments from the hero’s life are subject to the laws of fictionalization and at the same time are a manifestation of reality due to the participation of the actor — a transgender person. Combining facts with fiction, the past with the present and destroying the theatrical illusion are activities that emphasize the emancipatory, discursive and causative potential of the spectacle, resulting in the creation of an affective community of event participants.